أبو الأعلى المودودي ومنهجه التربوي في تفسيره تفهيم القرآن - نيا، محمود حقيقت (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research aims to explore Al Mawdudi educational thought of his principles, general objectives and Qur'anic approach in raising individuals, family and the Muslim community. It also probes Mawdudi's approach to nurture the spirit, mind and body. In order to realize these objectives, the research employs the deductive analytical method to highlight the principles and general objectives of Mawdudi's thought and explanations, and traces its educational significance. This research has five chapters, excluding the introductory chapter, which presents the limitation of the research, its objectives and importance, and a review of previous studies on some aspects of Mawdudi's thought. The first chapter examines Mawdudi biography, giving an overview of his life and efforts in the field of education and advocacy (preaching or call) through the Islamic group. His publications and some important features of his reformative call are also discussed in the same chapter. The second and the third chapters focus on his Qur'anic explanation, Tafhim Al-Qur'an, its characteristics, the analysis of the views of scholars on it, and the impact of the exegesis on Muslims. Indeed, Imam Mawdudi had felt an urgent need to write an interpretation of the Qur'an which would be accessible to readers and help them understand the Qur'an correctly. Although the Nobel Qur'an has been among Muslims and they read it widely, there is, however, a manifest problem which made the Qur'an to be ignored and left unapplied in several aspects of life. Mawdudi has felt that he could not explain religion and its features, but through the book of Allah, and that he wants to make this interpretation an approach to raise members of the Islamic group. The fourth and fifth chapters focus on Mawdudi's approach towards raising individuals, family and the Muslim nation. He has written four books on the method of education for members of the Islamic society; these are: “Tadhkiratu ya du'atul Islam”, “Al-Islam wa tazkiyatun nafs”, “As-salahu wal fasadu” and “Annazariyyatul Islami Al-akhlaqhiyyah”. Actually, the principles of Mawdudi's advocacy and objectives could be summarized into three Tawhid (monotheism), Tazkiyah (purification) and work towards restoring the rule of Allah on earth. Mawdudi felt that the major obstacle which impedes the application of Islamic educational thought lies in the misconception of the necessities of the principles of thought and behavioral significance. Therefore, he did not limit himself to mere correction of cognitive concepts in theory; but employed all necessary practical means of reformation in the process of educating and training members of the Islamic group.